2008
DOI: 10.1002/dvdy.21632
|View full text |Cite
|
Sign up to set email alerts
|

Lifespan extension and increased pumping rate accompany pharyngeal muscle‐specific expression of nfi1 in C. elegans

Abstract: Caenorhabditis elegans nfi-1 belongs to the Nuclear Factor I (NFI) family of transcription factors known to regulate metazoan gene expression and development. We showed previously that loss of nfi-1 in worms results in multiple behavioral defects; slower pharyngeal pumping rate, impaired egg laying, defective motility, and a shortened life span. Here, we generated cell-type specific transgenic worms to determine the cells in which nfi-1 must be expressed to rescue the pharyngeal pumping defect. Expression of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
(18 reference statements)
2
6
0
Order By: Relevance
“…This PWM is very similar to the known motif for the TF Pha4, which is known to direct transcription of pharyngeal genes (Gaudet and Mango 2002). In accordance with previous reports that NFI-1 is expressed in muscles (mainly pharynx and head muscles), neurons and intestinal cells (Lazakovitch et al 2005, 2008), our corresponding motif (H01M10.2.1) is also enriched for genes whose GFP-fused promoters are expressed in the pharynx ( P < 3 × 10 −5 ) and body wall muscle ( P < 7 × 10 −3 ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This PWM is very similar to the known motif for the TF Pha4, which is known to direct transcription of pharyngeal genes (Gaudet and Mango 2002). In accordance with previous reports that NFI-1 is expressed in muscles (mainly pharynx and head muscles), neurons and intestinal cells (Lazakovitch et al 2005, 2008), our corresponding motif (H01M10.2.1) is also enriched for genes whose GFP-fused promoters are expressed in the pharynx ( P < 3 × 10 −5 ) and body wall muscle ( P < 7 × 10 −3 ).…”
Section: Resultssupporting
confidence: 91%
“…Figure 1 shows three different classes of conserved elements that emerge from this analysis. The PWM H01M10.2.1 is likely to represent the binding motif for the TF nuclear factor I-1 (NFI-1) on the basis of several types of evidence: (1) it is highly similar to the documented NFI-1 binding site (Whittle et al 2009) and the vertebrate NF-1 binding site (TRANSFAC AC number: M00056); (2) the gene cluster associated with the H01M10.2.1 matrix is significantly enriched for the known NFI-1 target genes (Whittle et al 2009) ( P < 10 −14 ); (3) the gene cluster associated with the H01M10.2.1 matrix is significantly enriched for genes that are expressed in pharynx ( P < 3 × 10 −5 ) and body wall muscle ( P < 7 × 10 −3 ), which is consistent with observed NFI-1 expression in C. elegans (Lazakovitch et al 2005, 2008); (4) H01M10.2.1 is significantly correlated to NFI-1 ChIP samples ( P < 10 −6 ; t -value ~15.6); and (5) the gene cluster associated with the H01M10.2.1 matrix is significantly enriched for GO terms that are consistent with NFI-1’s function.…”
Section: Resultssupporting
confidence: 72%
“…Loss of nfi-1 in C. elegans results in a decreased rate of pharyngeal pumping, impaired egg-laying, altered motility, and a shortened lifespan (6). NFI-1 seems to function autonomously in the pharyngeal muscle with respect to pumping and lifespan (7).…”
mentioning
confidence: 99%
“…The nematode Caenorhabditis elegans is a model organism very frequently used to study aging. Its pharynx is one of the most essential organs; it is contracted through a coordinated process to perform food intake and distribute it to the animal's digestive tract [11]. Aging has been associated with pumping rate alterations and it has been suggested that the pumping rate can be used as a predictor of lifespan, as prolonged lifespan of the nematode C. elegans has been associated with an increased pumping rate [12].…”
Section: Introductionmentioning
confidence: 99%